2021
DOI: 10.1186/s43141-021-00175-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a novel β-defensin isoform from the red-toothed trigger fish, Odonus niger (Ruppel, 1836)

Abstract: Background The concern regarding a post-antibiotic era with increasing drug resistance by pathogens imposes the need to discover alternatives for existing antibiotics. Antimicrobial peptides (AMPs) with their versatile therapeutic properties are a group of promising molecules with curative potentials. These evolutionarily conserved molecules play important roles in the innate immune system of several organisms. The β-defensins are a group of cysteine rich cationic antimicrobial peptides that pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 73 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…Wang and coworkers have demonstrated the cytokine-like properties of HMGB1 and also established HMGB1 as a prototype for endogenous danger signals or the so-called “Alarmins” [ 18 , 20 ]. Roles of HMGB1 as an alarmin signal were also reported in a study based on a group of critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang and coworkers have demonstrated the cytokine-like properties of HMGB1 and also established HMGB1 as a prototype for endogenous danger signals or the so-called “Alarmins” [ 18 , 20 ]. Roles of HMGB1 as an alarmin signal were also reported in a study based on a group of critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…HBD3 has significant bactericidal activity. It helps with chemoattraction and adaptive immunity [ 18 ]. Studies have shown that the levels of HBD3 levels increase during the acute phase of bacterial infection [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel β -defensin, called On-Def, was studied from red-toothed triggerfish, Odonus niger . It was isolated from gill mRNA [ 151 ]. The most recent immunomodulatory chemical constituents isolated from marine macroorganisms that are mentioned in the text are listed in Table 2 .…”
Section: Macroorganisms As Source Of Immunomodulatory Compoundsmentioning
confidence: 99%